HUBUNGAN DAYA TAHAN OTOT LENGAN TERHADAP HASIL TEMBAKAN 30 M PADA ATLET PANAHAN PPLP DISPORA RIAU TAHUN 2016 - ', Muslim; ', Saripin; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s observation of Archery Athlete PPLP of Education And Sports Departement of Riau 2016 Researcher found the low of the arm muscles endurance at the time of draw arrows so the athletes to repeat the draw arrows. It influences phsycal condition that is the arm muscles endurance. The purpose of this research is to see how much the correlation of the arm muscles endurance to the result of 30 m shooting of Archery Athlete PPLP of Education And Sports Departement of Riau 2016. Population in this research were all male students who were 8 people and all female student who were 4 people. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 12 people. Research instrument used push up test and 30 M shooting test. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : there is correlation of the arm muscles endurance to the result of 30 M shooting of Archery Athlete PPLP.Key word : arm muscles endurance, 30 M shooting.